2015
DOI: 10.1159/000437291
|View full text |Cite
|
Sign up to set email alerts
|

Peritonitis following Endoscopy in a Patient on Peritoneal Dialysis with a Discussion of Current Recommendations on Antibiotic Prophylaxis

Abstract: Patients on peritoneal dialysis (PD) are at increased risk for peritonitis. We report a case of a patient with end-stage renal disease on continuous ambulatory PD (CAPD) who developed peritonitis within 24 h of upper endoscopy with biopsy and colonoscopy with polypectomy. He had a previous history of peritonitis unrelated to invasive procedures and eventually was transitioned to hemodialysis because of his recurrent peritonitis. The International Society for Peritoneal Dialysis (ISPD) and newly revised America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
6
0
4
Order By: Relevance
“…Peritonitis may arise from transmural migration of bacteria from the bowel to the peritoneal cavity after manipulation of the gastrointestinal tract [2]. Several reports have described the development of peritonitis in PD patients who underwent GI endoscopy without prophylaxis [3, 4, 5, 6], and a retrospective study found that the risk of peritonitis after colonoscopy without antibiotic prophylaxis was 6.3% [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peritonitis may arise from transmural migration of bacteria from the bowel to the peritoneal cavity after manipulation of the gastrointestinal tract [2]. Several reports have described the development of peritonitis in PD patients who underwent GI endoscopy without prophylaxis [3, 4, 5, 6], and a retrospective study found that the risk of peritonitis after colonoscopy without antibiotic prophylaxis was 6.3% [7].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have described the development of peritonitis in PD patients who underwent GI endoscopy without prophylaxis [3, 4, 5, 6], and a retrospective study found that the risk of peritonitis after colonoscopy without antibiotic prophylaxis was 6.3% [7]. Peritoneal fluid in these patients has yielded gram-positive and gram-negative organisms [2, 8]. The CDC group EO-3 organism has been reported to cause peritonitis in a PD patient [9].…”
Section: Discussionmentioning
confidence: 99%
“…No existen estudios que evalúen el riesgo de infección de prótesis ortopédicas en procedimientos gastrointestinales considerados de alto riesgo para bacteriemia como dilatación de estenosis esofágicas, biopsia por ultrasonido endoscópico y colangiografía retrógrada (Tabla 3); sin embargo, la frecuencia de bacteriemia es menor al 22% en estos casos en comparación con actividades de la vida diaria como cepillarse los dientes o uso de hilo dental, con una incidencia de bacteriemia de hasta el 68% 48 .…”
Section: Prótesis Ortopédicasunclassified
“…El desarrollo de peritonitis en pacientes bajo tratamiento con diálisis peritoneal continua ambulatoria (DPCA) es un evento asociado con aumento en costos de tratamiento 48 , importante morbilidad e incluso mortalidad 49,50 de hasta un 5% 51 . Cuando la peritonitis es por bacterias gramnegativas (como aquellas de origen enteral) se asocia con un peor pronóstico 49 .…”
Section: Diálisis Peritoneal Continua Ambulatoriaunclassified
See 1 more Smart Citation